Dentinal hypersensitivity: review of aetiology, differential diagnosis, prevalence, and mechanism - Al-Sabbagh, M; Andreana, S; Ciancio, S G (Journal of the International Academy of Periodontology, 2004)
Dentinal hypersensitivity is a painful response to a non-noxious stimulus applied to exposed dentine in the oral environment. Dentine exposure results from a combination of two or more aetiological factors that lead to loss of enamel and/or loss of cementum. The hydrodynamic theory is the most accepted theory that explains the excitement of pulpal nerve fibres by a stimulus applied to the exposed dentine. Dentinal hypersensitivity had been reported to affect middle age people most often with no gender differences and has been shown to be influenced by tooth location.